2022
DOI: 10.3390/ijms23063040
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficacy of ZnO Nanostructures against SARS-CoV-2

Abstract: In 2019, the new coronavirus disease (COVID-19), related to the severe acute respiratory syndrome coronavirus (SARS-CoV-2), started spreading around the word, giving rise to the world pandemic we are still facing. Since then, many strategies for the prevention and control of COVID-19 have been studied and implemented. In addition to pharmacological treatments and vaccines, it is mandatory to ensure the cleaning and disinfection of the skin and inanimate surfaces, especially in those contexts where the contagio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…As a result, ZnO nanoparticles are found to regulate medication dosage on the SARS-CoV-2 target. Later Sportelli et al 274 reported the experimental approach for the ZnO nanoparticles to lower the antigen of SARS-CoV-2 by about 90%. The ZnO nanoparticles are synthesized with the galvanostatic approach in the presence of different stabilizers.…”
Section: Zno Based Systems For Covid-19 Detectionmentioning
confidence: 99%
“…As a result, ZnO nanoparticles are found to regulate medication dosage on the SARS-CoV-2 target. Later Sportelli et al 274 reported the experimental approach for the ZnO nanoparticles to lower the antigen of SARS-CoV-2 by about 90%. The ZnO nanoparticles are synthesized with the galvanostatic approach in the presence of different stabilizers.…”
Section: Zno Based Systems For Covid-19 Detectionmentioning
confidence: 99%
“…The most likely mechanism includes a potential attachment with viral virions (spike proteins) and blocking the host receptors ACE2 for interaction, internalization of ZnO NPs inhibit early viral replication cycle followed by the release of zinc ions which disturb the plasmid/viral integrity; lastly, reactive oxygen species are produced photo catalytically to potentially deprive lipid/ protein, and nucleic structure of SARS CoV2. At very low concentrations (10µM), zinc ions can inhibit ACE2's capacity to metabolize substrates to provide antiviral effects ( Sportelli et al, 2022 ).…”
Section: Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…When tested in vitro, the PDDA-ZnO NPs induced a decrease in viral load between 70% and 90%; however no contribution was given by PDDA itself to the antiviral activity of the system. Then, PDDA-ZnO NPs were embedded into polyethylene oxide (a biodegradable and non-toxic polymer) film to reach a coating for frequently touched surfaces, with promising results, despite the polymeric material limiting the active surface of ZnO NPs to exert ionic release and subsequent antiviral activity [ 123 ].…”
Section: Nanomaterials For Covid-19 Prevention and Treatmentmentioning
confidence: 99%